Formation and Properties of Fibrin Clots Resulting from Staphylocoagulase (SC) Action - Kopeć, M; Węgrzynowicz, Z; Budzyński, A. Z; Jeljaszewicz, J; Latallo, Z. S; Lipiński, B; Kowalski, E (Thrombosis and Haemostasis, 1967)
Some properties of the fibrin clots formed under the influence of staphylocoagulase (SC) and thrombin were compared.1. Mechanical properties of SC-induced clots were found to be different from thrombin-induced clots. Maximal amplitude in TEG was significantly smaller in the case of SC.2. In the system containing all other necessary components for fibrin stabilization, SC in contrasts to thrombin did not produce stabilized clots. It was shown that this was due to the lack of FSF activation by SC. SC induced fibrin was easily stabilized by the addition of FSF activated by thrombin. No difference in sialic acid content has been found when SC and thrombin induced fibrins were compared.3. Neither clotting nor esterase activity of SC were inhibited by heparin and hirudin.4. Fibrinogen degradation products (FDP) inhibit clotting activity of SC. Both early and late FDP seem to affect this activity in a similar degree, whereas early FDP show much more pronounced effect in the case of thrombin induced clotting.5. The SC-clots are much more resistant to plasmin action, although SC itself does not inhibit plasmin caseinolytic activity.6. The significance of these findings is discussed.